The Naturals / [book 1] - Barnes, Jennifer Lynn, 1983- (Quercus, 2023)
Cassie is a natural at reading people. Piecing together the tiniest details, she can tell you who you are and what you want. But it's not a skill that she's ever taken seriously until the FBI come knocking: they've begun a classified programme that uses exceptional teenagers to crack infamous cold cases, and they need Cassie. What Cassie doesn't realise is that there's more at risk than a few unsolved murders - especially when she's sent to live with a group of teens whose gifts are as unusual as her own. Soon, it becomes clear that no one in the Naturals program is what they seem. And when a new killer strikes, danger looms close. Caught in a lethal game of cat and mouse with a killer, the Naturals are going to have to use all of their gifts just to survive . . .